Single and interactive effects of Varroa destructor, Nosema spp., and imidacloprid on honey bee colonies (Apis mellifera). Issue 8 (13th August 2018) - van Dooremalen, Coby; Cornelissen, Bram; Poleij‐Hok‐Ahin, Chula; Blacquière, Tjeerd
Abstract: High losses of honey bee colonies in recent decades are of great societal and economical concern and experienced as a sign of the vulnerability of the environment, including the service of crop pollination, and of the beekeeping sector. There is no single cause for the colony losses, but many contributing stressors may act in concert. Varroa destructor infestation is acknowledged as an important cause of these losses. The roles of infestation by Nosema ceranae or exposure to insecticides are controversial. Interactions between exposure to pesticides and V. destructor or Nosema spp. have previously been implicated. In two years of field experiments, we studied the effects of and possible interactions between the stressors V. destructor infestation, Nosema spp. infestation, and chronic sublethal exposure to a field‐realistic dose of the insecticide imidacloprid on the performance and survival of honey bee colonies. Colonies highly infested by V. destructor were 13% smaller in size and were 59.1 times more likely to die than colonies infested with low levels of V. destructor . Infestation with high levels of Nosema sp. led to 2% decrease in size and 1.4 times higher likelihood to die compared to colonies with low levels of Nosema sp. No effects of chronic sublethal exposure to imidacloprid on colony size or survival were found in this study. Exposure to V. destructor and imidacloprid led to a slightly higher fraction of bees infested with Nosema sp., but in contrast to the expectations, no resulting interactions were found for colony size or survival. Colonies as a superorganism may well be able to compensate at the colony level for sublethal negative effects of stressors on their individuals. In our experimental study under field‐realistic exposure to stressors, V. destructor was by far the most lethal one for honey bee colonies.